Durability testing and characterization of POM gears. (June 2021) - Hribersek, M.; Erjavec, M.; Hlebanja, Gorazd; Kulovec, Simon
Highlights: Wear measurement along the tooth flank with a 3D measurement microscope. The highest wear appears in the running-in phase. Higher temperature and gear deformations result in higher wear rate. Minimal linear wear is achieved by a modification of the tip and/or root relief. Abstract: Polymer gears are widely used in various power train applications, depending on the input requirements such as weight, noise emissions, load, operating temperature, load cycles, price of the product, etc. Power train systems often use polymers due to their advantageous properties. An optimal material combination should be selected during design to meet the above listed input requirements. The paper contributes to the understanding of wear mechanism in a time sequence from the start up to failed gear, where steel/POM gear pair material is of interest. Gear geometry, quality, testing arrangement and procedure are disclosed in this context. Propagating flank wear is observed by a 3D optical scanning device. Spot temperature of meshing gears is recorded during testing and presented in the study. The paper novelty is the approach for wear characterization throughout the POM gear lifetime. The contribution is the development of a procedure for defining wear progression across the entire tooth flank profile depending on test timescale. Additionally, wear coefficients are calculated according to VDI 2736 guidelines to improve the understanding of the wear progress during the entire service life of the gear pair.